2007
DOI: 10.1111/j.1365-2052.2007.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mtDNA sequences shows Japanese native chickens have multiple origins

Abstract: In this study, we analysed the mitochondrial DNA D-loop region of Japanese native chickens to clarify their phylogenetic relationships, possible maternal origin and routes of introduction into Japan. Seven haplogroups (Types A-G) were identified. Types A-C were observed in Jidori, Shokoku and related breeds. However, Type C was absent in Shokoku, which was introduced from China, while most Indonesian native chickens were included in the Type C haplogroup. Types D-G were observed in Shamo and related breeds. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
151
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(174 citation statements)
references
References 13 publications
17
151
5
1
Order By: Relevance
“…The median-joining (MJ) network analysis of the mtDNA D-loop haplotypes observed in Tanzanian local chickens, together with most frequently observed haplotypes from Liu et al (2006) and Oka et al (2007) as a skeletal frame reference, is shown in Figure 4. Twenty-three haplotypes were observed in Tanzanian chickens and were found to cluster with haplogroups D and E identified by Liu et al (2006 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median-joining (MJ) network analysis of the mtDNA D-loop haplotypes observed in Tanzanian local chickens, together with most frequently observed haplotypes from Liu et al (2006) and Oka et al (2007) as a skeletal frame reference, is shown in Figure 4. Twenty-three haplotypes were observed in Tanzanian chickens and were found to cluster with haplogroups D and E identified by Liu et al (2006 …”
Section: Resultsmentioning
confidence: 99%
“…Besides the sequences of the Tanzanian chicken populations, the network analysis included the most frequent haplotypes of nine clades from Liu's network and of three clades from Oka's, which were used as a reference frame in haplotype analysis (Liu et al, 2006;Oka et al, 2007). The list of haplotypes and their GenBank accession numbers are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…([9]; Japanese domestic chickens); Kanginakudru et al . ([11]; Indian domestic chickens and G. gallus murghi ) and Silva et al .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore two assumptions can be made from these data: (1) the wild population carrying haplogroup E has not been sampled yet, and sampling effort within the natural distribution range of G. g. murghi is needed; (2) this haplogroup belongs to an ancestral population from the Indian subcontinent that is now extinct. Furthermore, Haplogroup C has mainly been found in Japanese breeds that originate from commercial exchanges with Korea, Taiwan or the eastern provinces of China [9]. This haplogroup is also frequently present in breeds from the Chinese Guangdong province (Figure 4; Huxu breed: 100% and Qinyuan breed: 67%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation